Newly forming bone graft: a novel surgical approach to the treatment of denuded roots - Adriana Campos Passanezi Sant'Ana; Bruna F. Rahal Ferraz; Maria Lúcia Rubo de Rezende; Sebastião Luiz Aguiar Greghi; Carla Andreotti Damante; Euloir Passanezi (University of São Paulo, 2012)
Many techniques have been proposed for root coverage. However, none of them presents predictable results in deep and wide recessions. OBJECTIVES: The aim of this case series report is to describe an alternative technique for root coverage at sites showing deep recessions and attachment loss >4 mm at buccal sites. MATERIAL AND METHODS: Four patients presenting deep recession defects at buccal sites (>4 mm) were treated by the newly forming bone graft technique, which consists in the creation of an alveolar socket at edentulous ridge and transferring of granulation tissue present in this socket to the recession defect after 21 days. Clinical periodontal parameters, including recession depth (RD), probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP), plaque index (PI) and keratinized gingiva width (KGW) were evaluated by a single examiner immediately before surgery and at 1, 3, 6 and 9 months postoperatively. RESULTS: All cases showed reduction in RD and PD, along with CAL gain, although no increase in KGW could be observed. These findings suggest that the technique could favor periodontal regeneration along with root coverage, especially in areas showing deep recessions and attachment loss.